Land-Development offset policies in the quest for sustainability: what can China learn from Germany? - Tan, Rong; Wang, Rongyu; Sedlin, Thomas (MDPI, 2014)
Land-development offset policies consist of measures that require compensation to be made for the negative impact of land development on agricultural production, ecological and environmental conservation, and the sustainability of economic and social development. However, when such policies are inappropriately designed, unexpected problems can result. This paper describes certain land-development offset policies that have recently been implemented in China, with a particular emphasis on three such policies: the Balancing Policy, the Linkage Policy, and the Integrated Policy. These well-intentioned environmental policies have led to unexpected ecological, social, and cultural problems. This paper also describes the core of German land-development policy, which features a distinctive compensation system that has been employed since the 1970s, and compares Chinese and German land-development policies to highlight differences in three main areas: policy purposes, governance structures, and fundamental institutions. The comparisons might help explain the unexpected outcomes in China, and they also lead to land-development offset policy recommendations for China in the near future.
Keywords: Umweltschutz; Boden; Landwirtschaftliche Fläche; Flächennutzung; Bauland; Bodenpolitik; Flächenverbrauch; Internationaler Vergleich; Flächenkonversion